2013
DOI: 10.2190/om.66.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Perceptions of Effects of a Student's Death: A Phenomenological Study

Abstract: When a student dies in a school setting many school professionals step in and offer grief services to the students affected. In the classrooms, teachers are expected to step in and help the students grieve; however, equivalent support for teachers seems to be lacking. This study explored the lived experiences of teachers who experienced the unanticipated death of a student. From the analysis, the following themes emerged: (a) releasing feelings, (b) resources (c) lost academic time and redirection, and (d) hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…If schools provide help, they are often more likely to do this immediately after a death, and students experiencing long-term effects of grief may be overlooked, as students without overt symptoms can be (Hedman, 2012;Pfefferbaum et al, 2000). Although teachers are expected to help grieving students, many feel that they are not trained to handle a student's death, and additional professional development in the area of crisis response training are often needed (Dyregrov, Dyregrov, & Idsoe, 2013;Hart & Garza, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If schools provide help, they are often more likely to do this immediately after a death, and students experiencing long-term effects of grief may be overlooked, as students without overt symptoms can be (Hedman, 2012;Pfefferbaum et al, 2000). Although teachers are expected to help grieving students, many feel that they are not trained to handle a student's death, and additional professional development in the area of crisis response training are often needed (Dyregrov, Dyregrov, & Idsoe, 2013;Hart & Garza, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that the teachers were unable to deal with the incident directly and talked about it only indirectly. Most indicated the need for additional resources during the crisis such as counseling and psychologist support (Hart & Garza, 2013).…”
Section: Coping With the Death Of A Student Among Homeroom Teachersmentioning
confidence: 99%
“…The death of an adolescent affects classmates, school staff, and teachers who taught the student (Hart & Garza, 2013). The homeroom teacher plays a central role in her students’ adjustment and must provide the best possible response to their needs arising from the experience of loss.…”
Section: Introductionmentioning
confidence: 99%
“…That literature does not address college faculty member grief or, for the most part, even indicate that it might exist. Ayers (2015), Hart and Garza (2012), and Rowling (1995Rowling ( , 2003, writing about K-12 teachers, did address teacher grief. Ayers mentioned (p. 86), without citing specifics, a web posting about K-12 teacher grief when a student dies which received responses from hundreds of teachers who talked about their own grief at a student's death.…”
Section: Neglect Of Faculty Grief In the Academic Literaturementioning
confidence: 99%
“…7-8). Hart and Garza (2012) highlighted the need for teachers to release feelings, issues of lost academic time resulting from a student death, the lack of institutional resources for dealing with a student death, and the desire to honor the memory of students who have died. Rowling wrote about cultural (my term), institutional, and personal factors that might disenfranchise a teacher who is grieving, among other things, student death or close calls to death.…”
Section: Neglect Of Faculty Grief In the Academic Literaturementioning
confidence: 99%